Multidimensional perspectives on (bio)markers: Linking clinical and biological insights across psychiatric disorders, supporting a transdiagnostic model - Dusan Hirjak (Biomarkers in Neuropsychiatry)
This editorial serves as an introduction to the Special Issue ''Biomarkers of Trans-Nosological Functional Domains'', offering an overview of its central themes and contributions.